Modern Condition of Natural foci Tick-Borne Infections in Altay Republic - S. A. Rudakova; L. D. Schuchinova; L. V. Schuchinov; N. V. Rudakov; A. F. Lubenko; M. G. Mal’Kova (Эпидемиология и вакцинопрофилактика)
The presence of common vectors of various pathogens determines the high prevalence of combined natural foci of tick-borne infections in Altay Republic. The current state of natural foci is presented in terms of the spectrum of key pathogens transmitted by ticks. Morbidity of major diseases transmitted by the bite of ticks was analyzed.